Ultra-processed food consumption in UK adolescents: distribution, trends, and sociodemographic correlates using the National Diet and Nutrition Survey 2008/09 to 2018/19. - Chavez-Ugalde, Irazu Yanaina; de Vocht, Frank; Jago, Russell; Adams, Jean; Ong, Ken K.; Forouhi, Nita G.; Colombet, Zoé; Ricardo, Luiza I. C.; van Sluijs, Esther; Toumpakari, Zoi (European Journal of Nutrition, 2024)
Purpose: We quantified levels of ultra-processed food (UPF) consumption and investigated consumption patterns in a representative sample of UK adolescents. Methods: We used data from 4-day food diaries from adolescents in the UK National Diet and Nutrition Survey (NDNS) (2008/09–2018/19). UPF were identified using the NOVA classification. We estimated the percentage of Total Energy Intake (%TEI) and the absolute weight (grams). Linear regression models quantified differences in UPF consumption across survey years and its association with participant's individual characteristics. This was an analysis of the repeated cross-sectional data from the UK NDNS Rolling Programme waves 1–11 (2008/09–2018/19). A total of 2991 adolescents (11–18y) with complete information on dietary intake were included. Results: Mean UPF consumption was 861 (SD 442) g/d and this accounted for 65.9% (SD 13.4%) of TEI. Between 2008 and 2019, mean UPF consumption decreased from 996 to 776 g/d [ – 211 (95%CI – 302; – 120)] and from 67.7% to 62.8% of TEI [ – 4.8% (95%CI – 8.1; – 1.5)]. Higher %TEI was consumed by adolescents with lower socioeconomic status; white ethnicity and living in England North. A higher weight of UPF consumption (g/d) was associated with being male, white, age 18y, having parents with routine or manual occupation, living in England North, and living with obesity. Conclusion: Average energy intake from UPF has decreased over a decade in UK adolescents. We observed a social and regional patterning of UPF consumption, with higher consumption among adolescents from lower socioeconomic backgrounds, from a white ethnicity and living in England North. Our findings suggest inequalities associated with UPF intake and factors that might lie beyond individual choice.